Assessment of Financial Performance of Agricultural Cooperative Unions: The Case of West Harerghe Zone, Oromia Region, Ethiopia - Bonsa, Buta Debela; Ebrahim, Kerima Rahmeto (Archives of Business Research, 2020)
Financial statement analysis involves comparing cooperative union performance and evaluating trends in the unions’ financial position over time. Managers use financial statement analysis to identify situations demanding attention; potential lenders use financial analysis to determine whether the union is creditworthy; and stockholders use financial analysis to help predict future earnings, dividends, and free cash flow. This study is conducted on Assessment of Financial performance of Agricultural Cooperative unions: the Case of West Harerghe zone, Oromia region, Ethiopia. The general objective of this study was to evaluate financial performance of agricultural cooperative union. For this study, the researchers used both primary and secondary sources of data taken from purposively selected two cooperative unions (i.e. Burka Galeti and Chercher Oda bultum) since they do have audited financial statements out of five unions found in western Haraghe. The study also used FGD and interview with fiancé managers and employees of the union for further explanation. Based on the financial statement analysis the researchers found that the agricultural cooperatives are efficient and effective in asset utilization, activity and debt equity management ratios. However, the financial statement analysis showed that the current asset ratio is below the industry standard that cannot cover its short term liabilities form its current asset section of the balance sheet. Moreover, the profitability ratio of the unions revealed that the agricultural cooperative unions are efficient to make profit but the margin of profit is below 25% that cannot make the union successful to cover all the incidental costs that are borne within short and long-term periods. The OLS model revealed that quick, fixed asset turnover, total asset turnover, inventory turnover and gross profit margin ratios are significantly and positively affecting ROA. As a result, the researchers recommend that the agricultural cooperative unions are expected to improve its effective and efficient management of the day to day activities of the union. Furthermore, the unions are expected to higher managers who have the caliber to manage each and every activities of the union and who are visionary to bring success for the unions.